2020
DOI: 10.20517/2347-9264.2020.124
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for innervation of the neophallus

Abstract: A fundamental goal of phalloplasty includes the construction of a sensate neophallus. Both tactile and erogenous sensation are important for protective sensation (including retention of implantable penile prosthesis) as well as sexual satisfaction. This article will describe the sensory innervation of flaps commonly used for phalloplasty including the radial forearm flap, anterolateral thigh flap, and musculocutaneous latissimus dorsi flap. The sensory innervation of the perineum and external genitalia will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…It is clear that sensory outcomes are improved when direct nerve coaptation is performed; however, little granularity in current data is available beyond the presence or absence of sensation and ability to achieve orgasm, making quantification of sensory outcomes difficult. 6 , 7 A recent study reported results that often did not match patient expectations. 2 Other studies have demonstrated a range of sensory outcomes, with some patients reporting increased erogenous sensation and orgasmic intensity with hypersensitivity, and others reporting decreases in these same outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that sensory outcomes are improved when direct nerve coaptation is performed; however, little granularity in current data is available beyond the presence or absence of sensation and ability to achieve orgasm, making quantification of sensory outcomes difficult. 6 , 7 A recent study reported results that often did not match patient expectations. 2 Other studies have demonstrated a range of sensory outcomes, with some patients reporting increased erogenous sensation and orgasmic intensity with hypersensitivity, and others reporting decreases in these same outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Current strategies reported in the literature to optimize sensation following phalloplasty address mainly the peripheral components of sensation, focusing on the peripheral nerve coaptations that are performed during surgery. 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation